Pengaruh Pengangguran, Kemiskinan dan Indeks Pembangunan Manusia Terhadap Upah Minimum di Provinsi BantenTahun 2008-2023 - Albariq, Abid Dimas; Prasetyo, Andi Anugerah; Ilyas, Fakhry; Aryatama, Ravy Muhammad; Revaljo, Revaljo; Desmawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
During 2008-2023 , the Banten region experienced various social, monetary, and strategic changes that could affect the minimum wage level for the workforce. In this situation, it is important to distinguish the fundamental elements that affect the minium wage. such as unemployment, poverty, and Human Development Index (HDI).The purpose of this study is to determine how the influence of unemployment, poverty, and Human Development Index on the minimum wage in Banten province period 2008-2023. The Data used in this study is a time series data sourced from BPS Banten 2008-2023. This study uses the method of analysis of multiple linear regression using EVIEWS application. This study provides the results that unemployment (X1), poverty (X2) and Human Development Index (X3) simultaneously (together) significantly affect poverty (Y) in Banten province period 2008-2023.